2022
DOI: 10.1371/journal.pone.0261830
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s experience with the Arabin cervical pessary during pregnancy: A questionnaire survey

Abstract: Introduction The cervical pessary is used in women with precocious cervical ripening to prevent preterm birth. Up to now however, there have been no systematic studies on compliance and tolerance, which vary among different study cohorts. Material and methods A questionnaire was administered to 166 women treated with the Arabin cervical pessary in one center. Data were analysed about the patient’s experience before insertion (adequacy of information received), during treatment (follow-up, impact on daily lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The only characteristic that showed a signi cant association with method preference was the higher number of working hours in women with twin pregnancies, who preferred the pessary and P + P than ovules, with nine hours (9-10 h), nine hours (8-11 h), and eight hours (8-10 h), respectively (P = 0.02). 19.1 [17][18][19][20][21][22][23][24] 0.96…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only characteristic that showed a signi cant association with method preference was the higher number of working hours in women with twin pregnancies, who preferred the pessary and P + P than ovules, with nine hours (9-10 h), nine hours (8-11 h), and eight hours (8-10 h), respectively (P = 0.02). 19.1 [17][18][19][20][21][22][23][24] 0.96…”
Section: Resultsmentioning
confidence: 99%
“…The study also reported that the positive changes during the pessary treatment seemed to be related to a decreased concern about the risk of premature birth and to the relief of intrauterine pressure during daily activities. 17 The QoL may also play a role in the choice of treatment methods, particularly in cases of increased gestational risk resulting in unfavorable outcomes for both mother and fetus. [18][19][20] In singleton pregnancies, patients with a preference for the pessary over progesterone had higher scores in the environment domain.…”
Section: Comparison With the Results Of Previous Studiesmentioning
confidence: 99%
“…It is not surprising that authors of trials with recruitment below five patients per center 24 reported on high rates of patient discomfort, suggesting suboptimal application or reassurance. 40 Nicolaides and coworkers 22,23 determined that vaginal discharge following pessary placement was not due to bacterial pathogens as more than 40% of patients received essentially unindicated antibiotic therapy. Notably, antibiotics may have an impact on the vaginal microbiome and even induce PTB.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…Technical properties of different pessary types, (low) experience, and (insufficient) learning curves as reflected by the number of recruitments per center for the complete management were not reported in trials, a trend that has continued in a current “network meta‐analysis” (Mol et al submitted). It is not surprising that authors of trials with recruitment below five patients per center 24 reported on high rates of patient discomfort, suggesting suboptimal application or reassurance 40 . Nicolaides and coworkers 22,23 determined that vaginal discharge following pessary placement was not due to bacterial pathogens as more than 40% of patients received essentially unindicated antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%